The Hollars - Copley, Sharlot; Day, Charlie; Jenkins, Richard; Kendrick, Anna; Krasinski, John, 1979-; Martindale, Margo, 1951- (Culver City, CA : Sony Pictures Classics, 2016)
John Hollar, a struggling NYC artist is forced to navigate the small middle-American town he left behind when news of his mother's illness brings him home. Back in the house he grew up in, John is immediately swept up in the problems of his dysfunctional family, high school rival, and an over-eager ex-girlfriend as he faces impending fatherhood with his girlfriend in New York.
Sharlto Copley, Charlie Day, Richard Jenkins, Anna Kendrick, John Krasinski, Margo Martindale.
PG-13